Children and young people's experiences of completing mental health and wellbeing measures for research: learning from two school-based pilot projects - Ola Demkowicz; Emma Ashworth; Rosie Mansfield; Emily Stapley; Helena Miles; Daniel Hayes; Kim Burrell; Anna Moore; Jessica Deighton (BMC, 2020)
Abstract Background In recent years there has been growing interest in child and adolescent mental health and wellbeing, alongside increasing emphasis on schools as a crucial site for research and intervention. This has coincided with an increased use of self-report mental health and wellbeing measures in research with this population, including in school-based research projects. We set out to explore the way that children and young people perceive and experience completing mental health and wellbeing measures, with a specific focus on completion in a school context, in order to inform future measure and research design. Methods We conducted semi-structured interviews and focus groups with 133 participants aged 8-16 years following their completion of mental health and wellbeing measures as part of school-based research programmes, using thematic analysis to identify patterns of experience. Findings We identified six themes: Reflecting on emotions during completion; the importance of anonymity; understanding what is going to happen; ease of responding to items; level of demand; and interacting with the measure format. Conclusions Our findings offer greater insight into children and young people's perceptions and experiences in reporting on their mental health and wellbeing. Such understanding can be used to support more ethical and robust data collection procedures in child and adolescent mental health research, both for data quality and ethical purposes. We offer several practical recommendations for researchers, including facilitating this in a school context.